Significance of free radical oxidation in purulent process development in patients with chronic generalized periodontitis I-II severity degree. - Dronik, I. I. (Medicni perspektivi, 2014)
The results of the comparative study and the importance of free radical oxidation in causing purulent process in 46 patients with chronic generalized periodontitis I-II severity degree are presented. The aim - to study the characteristics of lipid peroxidation and antioxidant system in patients with generalized periodontitis, to establish the role of antiradical protection changes in suppurative inflammation in periodontal tissues. We found a substantial reduction of activity of key enzymes of antioxidant systems - superoxide dismutase and catalase in patients with chronic generalized periodontitis with suppuration of periodontal pockets, as compared with the rate in patients with septic foci in periodontal structures. It was stablished that lipid peroxidation is important in the development of purulent inflammation in periodontal tissues in patients with chronic generalized periodontitis, as evidenced by the significantly large accumulation of MDA and hydrate lipids in plasma and especially in the cellular elements of the blood (red blood cells) than in patients without this complication.